Diagnostic accuracy of placental growth factor and ultrasound parameters to predict the small‐for‐gestational‐age infant in women presenting with reduced symphysis–fundus height. (3rd July 2015) - Griffin, M.; Seed, P. T.; Webster, L.; Myers, J.; MacKillop, L.; Simpson, N.; Anumba, D.; Khalil, A.; Denbow, M.; Sau, A.; Hinshaw, K.; von Dadelszen, P.; et al.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2015; 46: 140–140